Superparamagnetic behavior of nanosized ZnFe2O4. (2018) - Dey, S.; Mondal, R.; Majumder, S.; Dasgupta, P.; Poddar, A.; Banerjee, S.; Kumar, S.
Abstract: Herein, we have reported the structural, microstructural, magnetic and hyperfine properties of nanosized (∼ 20 nm) ZnFe2 O4 synthesized by flow rate controlled coprecipitation method. The PXRD and HRTEM study demonstrate that the sample is nanosized, single phase spinel oxide which crystallizes in space group . The sample exhibits superparamagnetic relaxation above blocking temperature (∼ 25 K). The saturation magnetizations of the sample are 4, 20 and 28 emu g -1 at 300, 100 and 10 K, respectively and the sample exhibits no hysteresis at 300 and 100 K.